2002
DOI: 10.1136/bjsm.36.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on soluble transferrin receptor and other variables of the iron status

Abstract: Background: Soluble transferrin receptor (sTfr) is a new marker of iron status and erythropoietic activity. It has been included in multivariable blood testing models for the detection of performance enhancing erythropoietin misuse in sport. Objective: To evaluate the effect of different types and volumes of physical activity on sTfr concentration, variables of iron status (ferritin, transferrin, iron, and protein), and haematological indices. Methods: Thirty nine subjects were divided into three groups: 1, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
3
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 34 publications
11
72
3
10
Order By: Relevance
“…This is in accordance with other authors who reported increased blood or plasma volume in endurance athletes [11,20,26,33].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in accordance with other authors who reported increased blood or plasma volume in endurance athletes [11,20,26,33].…”
Section: Discussionsupporting
confidence: 82%
“…Nikolaidis et al [20] reported sTfR variability amounting to about 5% throughout a 24-h period of post-exercise recovery, the adjustments for plasma volume changes being non-significant. That low variability of sTfR and lack of significant correlations with training loads or CK activities observed in this study confirm the conclusions from earlier studies [14,16,20,23,26] and are indicative of a high stability of sTfR levels under conditions of intense exertions also in cross-country skiers.…”
Section: Referencessupporting
confidence: 81%
“…The results of this study disagreed with that of Schumacher et al, (2002) [20] who conducted a study on the effects of exercise on soluble transferring receptor and other variables of the iron status. 14 subjects were divided into two exercise tests, an incremental running test until exhaustion (test A) and a 45 minute constant speed running test at 70% Vo 2 max (test B).…”
Section: Discussioncontrasting
confidence: 55%
“…The concentration of sTfR increased immediately after exercise, as found in several studies. [11][12][13][14][15][16][17][18] The study of the long-term concentration of serum sTfR was carried out in a group of elite rugby players during a competitive season. 19 The sTFR concentration increased during the competition period and decreased at the end of the season.…”
Section: Groupmentioning
confidence: 99%